2012
DOI: 10.1007/s10144-012-0310-0
|View full text |Cite
|
Sign up to set email alerts
|

Stranded on an island: consequences of forest fragmentation for body size variations in an arboreal mammal, the edible dormouse (Glis glis)

Abstract: The island rule states that small mammals isolated on islands have the evolutionary tendency to become larger, while large mammals tend to become smaller. However, the underlying mechanisms and life history consequences of these insular shifts in body size still remain speculative. The aim of this study was to investigate whether an arboreal mammal, the edible dormouse (Glis glis), showed shifts in body size when inhabiting isolated forest fragments. We analysed a data set of 541 individuals captured between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…In accordance with patterns described by the island rule for small mammals, edible dormice inhabiting forest fragments were shown to be significantly larger and heavier than individuals in the continuous forest and occurred also in higher numbers [19]. The same pattern could also be found in different species of tree squirrels ( Sciurus carolinensis , S. niger and Tamiasciurus hudsonicus ) [24].…”
Section: Introductionsupporting
confidence: 83%
“…In accordance with patterns described by the island rule for small mammals, edible dormice inhabiting forest fragments were shown to be significantly larger and heavier than individuals in the continuous forest and occurred also in higher numbers [19]. The same pattern could also be found in different species of tree squirrels ( Sciurus carolinensis , S. niger and Tamiasciurus hudsonicus ) [24].…”
Section: Introductionsupporting
confidence: 83%
“…Indeed, Belding ground squirrels ( Spermophilus beldingi [= Urocitellus beldingi ]) do not achieve their maximum body size until the end of the second season of their life (Morton and Tung 1971). Fietz and Weis-Dootz (2012) also reported that growth occurred until at least the age of 4 years in edible dormice. In this study, 2- and 4-year-old individuals showed no difference in their body size, suggesting that garden dormice reach their adult size within the first 2 years, similar to Belding ground squirrels.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, the slope of this relation was close to 1 (0·98) indicating that variation in body mass directly reflects total body fat content. Therefore, although body mass is influenced by differences in structural size (Fietz & Weis‐Dootz ) or the size of other tissues (Bieber et al . ), it provides an excellent proxy of energy reserves in this species.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the slope of this relation was close to 1 (0Á98) indicating that variation in body mass directly reflects total body fat content. Therefore, although body mass is influenced by differences in structural size (Fietz & Weis-Dootz 2012) or the size of other tissues , it provides an excellent proxy of energy reserves in this species. For a subset of analyses that involved body mass loss (autumn/spring mass) during the hibernation season, we included data only for individuals whose mass was measured within 1 week of onset and termination of hibernation (n = 29).…”
Section: A N I M a L S A N D C L I M A T Ementioning
confidence: 99%